Outlook of India’s Real Estate Markets - Deshmukh, Hrishikesh (2009)
This dissertation is aimed at analyzing the Indian Economy from a Macroeconomic view point, with a particular focus on the real Estate sector. The focus on the Real Estate sector includes analyzing the various factors which come into play in the sector, understanding underlying variables and identifying investment opportunities. The economy of India has undergone superb change in the past few decades. The growth of GDP, averaging to a 6% per annum rate, is astounding. The growth in GDP has been primarily due to the liberalization of economic policies, growth in the talent pool of the country and development of various infrastructural facilities. With all so much happening, India is being discovered as a strong potential for investment, mainly in the services sector. The inflow of foreign funds has led to rapid expansion of industries, both service based and manufacturing based, and growth international trade. Growing number of households, rising disposable income levels and increase in financing options has opened up the real estate market in India to a whole new dimension of development. For this study, various research and analysis techniques have been adopted which will help in understanding and analyzing the subject matter.